Catechol modified activated carbon composite electrode material and preparation method and application thereof

By introducing and filling catechol into activated carbon to form a conductive network, the problem of poor stability and rate performance of activated carbon composite electrode materials in supercapacitors is solved, and the specific capacity and rate performance are improved, which is suitable for large-scale preparation.

CN119786274APending Publication Date: 2025-04-08LANZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411948441.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Among the existing supercapacitors, the poor stability, poor rate performance and low yield of activated carbon composite electrode materials limit their application in energy storage.

Method used

By introducing catechol into activated carbon, capillary action is used to fill the activated carbon framework to form a conductive network that is more conducive to electron/ion transmission, thereby improving the specific capacity and rate performance of activated carbon.

Benefits of technology

The EDLC-type specific capacity is improved under the high current of activated carbon, the pseudocapacitance specific capacity of composite materials is improved, and the problem of poor rate performance is solved. At the same time, the preparation process is simple, stable and controllable, and is suitable for large-scale large-scale preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786274A_ABST
    Figure CN119786274A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of supercapacitor materials, and particularly discloses a catechol modified activated carbon composite electrode material and a preparation method and application thereof. The preparation method of the composite electrode material comprises the following steps: adding a certain mass of activated carbon into a catechol solution, and dipping for 2-3 hours to form a mixed dispersion liquid; and then carrying out suction filtration on the mixed dispersion liquid under a vacuum condition, and drying in a drying oven overnight to obtain the product. The catechol is added into the activated carbon, the catechol and activated carbon particles can form a conductive network more beneficial to electron / ion transmission, an activated carbon framework is filled with catechol molecules through the capillary action, and the EDLC type specific capacity of the activated carbon under the large current density is improved. And meanwhile, catechol molecules can improve the pseudocapacitance type specific capacity of the composite material through a dual-electron redox system of the catechol molecules.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of supercapacitor materials, and specifically relates to a catechol-modified activated carbon composite electrode material and a preparation method and application thereof. Background Art

[0002] Supercapacitors are mainly composed of electrode materials, electrolytes, current collectors, diaphragm paper, and positive and negative electrode shells, among which electrode materials are the key factors affecting the electrochemical performance of supercapacitors. Electrode materials include carbon materials, conductive polymers, transition metal oxides, and other materials. Compared with conventional carbon materials, conductive polymers, MOFs, Mxenes, and transition metal oxides all have problems such as complicated preparation processes, high equipment costs, high environmental pollution, and poor stability of electrode materials, which hinder the development of supercapacitors.

[0003] Activated carbon among carbon materials has a simple preparation process, low cost and stable performance, making it widely used in the field of supercapacitor electrode materials since the advent of supercapacitors. Biomass raw materials such as coconut shells and fruit shells or by-products such as coal and petroleum are selected as precursors and then post-treated with high-temperature carbonization-activation or activation-high-pressure pyrolysis to obtain activated carbon. Physically activated activated carbon is mainly granular in shape, and its pore size distribution is mostly micropores. Its uncontrollable pore size distribution means that it cannot provide shorter ion diffusion paths and abundant ion storage active sites as an electrode material. It shows limited energy density and poor rate performance, which also limits its application in energy storage. Summary of the invention

[0004] The purpose of the present invention is to address the deficiencies in the prior art and provide a catechol-modified activated carbon composite electrode material and a preparation method and application thereof. The catechol molecules are filled into the activated carbon skeleton through capillary action to improve the EDLC-type specific capacity of the activated carbon under high current, so as to solve the technical problems of poor stability, poor rate performance and low yield of the activated carbon composite electrode material modified with transition metal-like oxides in the prior art.

[0005] To achieve the above object, the present invention adopts the following technical solution:

[0006] The first aspect of the present invention is to provide a method for preparing a catechol-modified activated carbon composite electrode material, comprising the following steps:

[0007] S1, preparing a solution of catechol with a concentration of 0.056 mol / L-0.448 mol / L using deionized water as a solvent at room temperature;

[0008] S2, adding a certain amount of activated carbon into the catechol solution and immersing for 2-3 hours to form a mixed dispersion;

[0009] S3. Filter the mixed dispersion under vacuum conditions, and then dry it in an oven overnight to obtain the catechol-modified activated carbon composite electrode material.

[0010] Furthermore, in step S2, the mass ratio of activated carbon to catechol is 0.05 to 0.4.

[0011] Furthermore, in step S2, the immersion temperature is 20°C to 25°C.

[0012] Furthermore, in step S3, the drying temperature is 50°C to 55°C.

[0013] The second aspect of the present invention is to provide a catechol-modified activated carbon composite electrode material prepared by the above-mentioned preparation method.

[0014] The third aspect of the present invention is to provide an electrode, comprising the above-mentioned composite electrode material and a one-dimensional or two-dimensional conductive agent.

[0015] Furthermore, the one-dimensional or two-dimensional conductive agent is one or more of carbon black, carbon whiskers, carbon fibers, carbon nanotubes or graphene.

[0016] The fourth object of the present invention is to provide a supercapacitor, comprising a positive electrode and a negative electrode, wherein the positive electrode is made of the above-mentioned electrode, and the negative electrode is made of the above-mentioned electrode.

[0017] Furthermore, it also includes a diaphragm, an inorganic electrolyte, lead terminals and a casing.

[0018] Furthermore, the structure of the supercapacitor is a wound cylindrical, wound square or stacked square structure, and its shell is an aluminum shell, a steel shell, or a soft-packaged plastic aluminum film.

[0019] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:

[0020] (1) The present invention provides a catechol-modified activated carbon composite electrode material. By adding catechol to activated carbon, catechol and activated carbon particles form a conductive network that is more conducive to electron / ion transmission. The catechol molecules are filled in the activated carbon skeleton through capillary action, which can improve the EDLC-type specific capacity of the activated carbon under high current. In addition, the catechol molecules can improve the pseudocapacitive specific capacity of the composite material through its two-electron redox system.

[0021] (2) The preparation method of a catechol-modified activated carbon composite electrode material of the present invention solves the problems of low specific capacity and poor rate performance of activated carbon by introducing catechol. The preparation method of the present invention is simple, the preparation conditions are stable and controllable, and large-scale mass production can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a comparison chart of the pore size distribution of original activated carbon and catechol-modified activated carbon provided in Example 5 of the present invention;

[0023] Figure 2 The adsorption isotherm diagram of catechol-modified activated carbon provided in Example 5 of the present invention;

[0024] Figure 3 is the adsorption isotherm of the original activated carbon;

[0025] Figure 4 50 mV·s of the supercapacitor of the original activated carbon and the catechol-modified activated carbon composite electrode material 6MKOH provided in Example 5 of the present invention -1 Cyclic voltammetry curves at different voltages under different scan rates;

[0026] Figure 5 The 2A·g of 6M KOH supercapacitor of the original activated carbon and the catechol-modified activated carbon composite electrode material provided in Example 5 of the present invention -1 Constant current charge and discharge curves under current density;

[0027] Figure 6 6M KOH supercapacitor Ragone diagram of original activated carbon and catechol-modified activated carbon composite electrode material provided in Example 5 of the present invention;

[0028] Figure 7 5A·g of 6MKOH supercapacitor of catechol-modified activated carbon composite electrode material provided in Example 5 of the present invention -1 Cyclic characteristics diagram under current density;

[0029] Figure 8 The cyclic voltammetric characteristic curves of the catechol-modified activated carbon composite electrode material 6MKOH soft-pack supercapacitor at different scan rates provided in Example 5 of the present invention;

[0030] Fig. 9 The constant current charge-discharge curves of the catechol-modified activated carbon composite electrode material 6MKOH soft-pack supercapacitor at different current densities provided in Example 5 of the present invention;

[0031] Fig.10 A physical picture of a 6M KOH soft-pack supercapacitor of the catechol-modified activated carbon composite electrode material provided in Example 5;

[0032] Fig.11 Schematic diagram of the pore structure of the original activated carbon and Example 5. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical scheme and advantages of the present invention clearer, the specific embodiments of the present invention are further described in detail below in conjunction with specific examples and drawings. If no specific test method, instrument or condition is specified in the examples, it is carried out according to the technology or condition described in the literature in this field or according to the product instructions. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.

[0034] The embodiment of the present invention provides a method for preparing a catechol-modified activated carbon composite electrode material, comprising the following steps:

[0035] Prepare catechol solutions of different concentrations;

[0036] The above solution is treated by stirring, and then a certain mass of activated carbon is added into the catechol solution and immersed for 2-3 hours to form a mixed dispersion, wherein the mass ratio of activated carbon to catechol is 0.05-0.4, and the stirring temperature is 20-25°C.

[0037] The mixed dispersion is filtered under vacuum conditions, and then dried in an oven overnight to obtain the catechol-modified activated carbon composite electrode material, wherein the drying temperature is 50-55°C.

[0038] In the embodiment of the present invention, the activated carbon is immersed in a catechol solution of a certain concentration, and the problem of low specific capacity and poor rate performance of the activated carbon is solved by introducing catechol.

[0039] In the preparation method of the embodiment of the present invention, the catechol molecules are immobilized on the surface and pore structure of low-cost and high specific surface area (SSA) activated carbon due to their high bonding force and redox reaction of the two-electron system during the preparation process. This allows the composite electrode material to have excellent cycle stability while significantly improving the specific capacity.

[0040] The activated carbon used in the embodiment of the present invention is commercial pure activated carbon XFP06, and its specific surface area is 1800 (±100) m 2 / g, particle size D 50 5±1μm.

[0041] The specific surface area of ​​Kuraray YP-80F activated carbon used in the present invention is 2100m 2 / g, particle size D 50 The specific surface area of ​​YEC-8B activated carbon is about 1800m 2 / g, particle size D 50 9μm.

[0042] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments and drawings. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.

[0043] Example 1

[0044] a. Prepare 1g of catechol into a 0.056mol / L solution and stir for 0.5h at a stirring rate of 600r / min. -1 , then immerse 400 mg of activated carbon in the above solution for 2-3 hours;

[0045] b. placing the mixed dispersion in a vacuum filtration device for vacuum filtration;

[0046] c. The composite product was placed in an oven for overnight drying, wherein the temperature of the oven was 50° C.; thus, a catechol-modified activated carbon composite electrode material was obtained.

[0047] Example 2

[0048] a. Prepare 2g of catechol into a 0.112mol / L solution and stir for 0.5h at a stirring rate of 600r / min. -1 , then immerse 400 mg of activated carbon in the above solution for 2-3 hours;

[0049] b. placing the mixed dispersion in a vacuum filtration device for vacuum filtration;

[0050] c. The composite product was placed in an oven for overnight drying, wherein the temperature of the oven was 50° C.; thus, a catechol-modified activated carbon composite electrode material was obtained.

[0051] Example 3

[0052] a. Prepare 4g of catechol into a 0.224mol / L solution and stir for 0.5h at a rate of 600r / min. -1 , then immerse 400 mg of activated carbon in the above solution for 2-3 hours;

[0053] b. placing the mixed dispersion in a vacuum filtration device for vacuum filtration;

[0054] c. The composite product was placed in an oven for overnight drying, wherein the temperature of the oven was 50° C.; thus, a catechol-modified activated carbon composite electrode material was obtained.

[0055] Example 4

[0056] a. Prepare 6 g of catechol into a 0.336 mol / L solution and stir for 0.5 h at a stirring rate of 600 r min.-1 , then immerse 400 mg of activated carbon in the above solution for 2-3 hours;

[0057] b. placing the mixed dispersion in a vacuum filtration device for vacuum filtration;

[0058] c. The composite product was placed in an oven for overnight drying, wherein the temperature of the oven was 50° C.; thus, a catechol-modified activated carbon composite electrode material was obtained.

[0059] Example 5

[0060] a. Prepare 6.88 g of catechol into a 0.3852 mol / L solution and stir for 0.5 h at a rate of 600 r min. -1 , then immerse 400 mg of activated carbon in the above solution for 2-3 hours;

[0061] b. placing the mixed dispersion in a vacuum filtration device for vacuum filtration;

[0062] c. The composite product was placed in an oven for overnight drying, wherein the temperature of the oven was 50° C.; thus, a catechol-modified activated carbon composite electrode material was obtained.

[0063] Example 6

[0064] a. Prepare 8g of catechol into a 0.448mol / L solution and stir for 0.5h at a rate of 600r / min. -1 , then immerse 400 mg of activated carbon in the above solution for 2-3 hours;

[0065] b. placing the mixed dispersion in a vacuum filtration device for vacuum filtration;

[0066] c. The composite product was placed in an oven for overnight drying, wherein the temperature of the oven was 50° C.; thus, a catechol-modified activated carbon composite electrode material was obtained.

[0067] Comparative Example 1

[0068] a. Soak 400 mg of activated carbon (XFP06) in water of the same volume as the above solution for 2-3 hours;

[0069] b. placing the mixed dispersion in a vacuum filtration device for vacuum filtration;

[0070] c. The composite product was placed in an oven for overnight drying, wherein the temperature of the oven was 50° C.; thus, a catechol-modified activated carbon composite electrode material was obtained.

[0071] Comparative Example 2

[0072] The method is basically the same as Example 5, except that resorcinol is used to obtain a resorcinol-modified activated carbon composite electrode material.

[0073] Comparative Example 3

[0074] The method is basically the same as Example 5, except that hydroquinone is used to obtain a hydroquinone-modified activated carbon composite electrode material.

[0075] Comparative Example 4

[0076] Basically the same as Example 5, except that Kuraray YP-80F activated carbon is used.

[0077] Comparative Example 5

[0078] Basically the same as Example 5, except that YEC-8B activated carbon is used.

[0079] Example 7

[0080] This embodiment provides an electrode.

[0081] The catechol-modified activated carbon obtained in Example 1-6 was used as the electrode material, and two pieces of nickel foam were cut, ultrasonically washed with anhydrous ethanol for 10 minutes, and the nickel foam was dried. 1-1.2 mg of the electrode material was weighed and sandwiched between two pieces of nickel foam. The nickel foam sandwiching the electrode material was wrapped with aluminum foil and placed on a tablet press with a pressure of 10 MPa and maintained for 10 seconds to obtain a working electrode.

[0082] Example 8

[0083] This embodiment provides a super capacitor.

[0084] Supercapacitor packaging: Take 2 pieces of nickel foam, wash them with anhydrous ethanol ultrasonically for 10 minutes, and dry the nickel foam. Weigh 1-1.2 mg of electrode material and sandwich it between two pieces of nickel foam. Wrap the nickel foam sandwiched with electrode material with aluminum foil and place it on a tablet press. Press it with 10 MPa pressure for 10 seconds and package it into a water-based (6M KOH) supercapacitor. Fig.10 shown.

[0085] The structural shape of the supercapacitor is not limited and can be a wound cylindrical shape, a wound square shape or a stacked square shape, and its shell is an aluminum shell, a steel shell, or a soft-packaged plastic aluminum film.

[0086] Supercapacitors were prepared using the electrode materials obtained in Examples 1-6 and Comparative Examples 1-5, and their electrochemical properties were tested (the instrument used for the supercapacitor test was Chenhua 660E, the working electrode was the prepared nickel foam electrode, the counter electrode was a platinum sheet electrode (10 mm × 10 mm × 1 mm), the reference electrode was a silver / silver chloride electrode, the electrolyte was a 6 M KOH solution, and the electrochemical test was performed using cyclic voltammetry (working voltage -1-0 V), constant current charge and discharge test (current density 1 A g -1 ) and equivalent impedance test (0.1Hz-100000Hz), the test results are shown in Table 1 below:

[0087] Table 1. Electrochemical properties of composite electrode materials prepared in various embodiments.

[0088]

[0089] As can be seen from the above table, the specific capacitance of the capacitor prepared from the composite electrode material prepared in Example 5 is much higher than the specific capacitance of the capacitor prepared from the pure activated carbon electrode (Comparative Example 1), and its specific capacitance is increased by 74%. This indicates that the graphene-modified activated carbon composite electrode material prepared by the preparation method of the embodiment of the present invention has excellent electrochemical properties.

[0090] refer to Figure 1-3 , which is a comparison diagram of the pore size distribution of the original activated carbon and the catechol-modified activated carbon provided in Example 5 of the present invention. The specific surface area is significantly reduced after modification.

[0091] refer to Figure 4 After catechol modification, the cv curve area becomes significantly larger, indicating that the specific capacity is significantly improved.

[0092] refer to Figure 5 The charge and discharge time of the catechol-modified activated carbon composite electrode material prepared in Example 5 is significantly longer than that of the original activated carbon.

[0093] refer to Figure 6 , are 6M KOH supercapacitor Ragone plots of the original activated carbon and the catechol-modified activated carbon composite electrode material prepared in Example 5 of the present invention, which are used to characterize the energy storage performance and power parameters of the device, respectively. The device prepared in Example 5 of the present invention has a power of 5.88Wh·kg -1 High energy density, compared to 3.82Wh·kg of activated carbon devices -1 The energy density of the material is greatly improved, which is determined by the pseudocapacitive functional groups and the rich pore structure.

[0094] refer to Figure 7 , is the cycle performance diagram of the 6M KOH supercapacitor button device of the catechol-modified activated carbon composite electrode material prepared in Example 5 of the present invention, 5A·g-1 The capacity retention rate is 100% after 10,000 cycles at a current density of .

[0095] refer to Figure 8 , is the cv curve of the 6M KOH supercapacitor soft-pack device of the catechol-modified activated carbon composite electrode material prepared in Example 5 of the present invention.

[0096] refer to Fig. 9 , is the GCD curve of the 6M KOH supercapacitor soft-package device of the catechol-modified activated carbon composite electrode material prepared in Example 5 of the present invention.

[0097] refer to Fig.10 , is an optical photograph of a 6M KOH supercapacitor soft-package device of the catechol-modified activated carbon composite electrode material prepared in Example 5 of the present invention.

[0098] refer to Fig.11 , is a schematic diagram of the pore structure of the original activated carbon and Example 5. The yellow lines in Figure b indicate that catechol is grafted on the micropores and surface.

[0099] In the embodiment of the present invention, a catechol-modified activated carbon electrode material is prepared by a simple impregnation process, which greatly improves the specific capacity, solves the problem of poor rate performance of the activated carbon material, and prepares a supercapacitor soft-pack device.

[0100] In the absence of conflict, the above embodiments and features in the embodiments may be combined with each other.

[0101] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a catechol-modified activated carbon composite electrode material, characterized in that: The following steps are involved: S1. Prepare a solution of catechol with a concentration of 0.056 mol / L to 0.448 mol / L using deionized water as a solvent at room temperature; S2, adding a certain amount of activated carbon into the catechol solution and immersing for 2-3 hours to form a mixed dispersion; S3. Filter the mixed dispersion under vacuum conditions, and then dry it in an oven overnight to obtain the catechol-modified activated carbon composite electrode material.

2. The preparation method according to claim 1, characterized in that In step S2, the mass ratio of activated carbon to catechol is 0.05 to 0.

4.

3. The preparation method according to claim 1, characterized in that: In step S2, the immersion temperature is 20°C to 25°C.

4. The preparation method according to claim 1, characterized in that: In step S3, the drying temperature is 50°C to 55°C.

5. A catechol-modified activated carbon composite electrode material prepared by the preparation method as described in claims 1 to 4.

6. An electrode, characterized in that: It comprises the composite electrode material as claimed in claim 5, and a one-dimensional or two-dimensional conductive agent.

7. The electrode according to claim 6, characterized in that The one-dimensional or two-dimensional conductive agent is one or more of carbon black, carbon whiskers, carbon fibers, carbon nanotubes or graphene.

8. A supercapacitor comprising a positive electrode and a negative electrode, characterized in that: The positive electrode is made of the electrode described in any one of claims 4 to 6, and the negative electrode is made of the electrode described in any one of claims 4 to 6.

9. The supercapacitor according to claim 8, characterized in that: It also includes a diaphragm, an inorganic electrolyte, lead terminals and a casing.

10. The supercapacitor according to claim 8, characterized in that: The structure of the supercapacitor is a wound cylindrical shape, a wound square shape or a stacked square shape, and its shell is an aluminum shell, a steel shell, or a soft-packaged plastic aluminum film.